2006
DOI: 10.1037/0012-1649.42.3.436
|View full text |Cite
|
Sign up to set email alerts
|

The language of online leadership: Gender and youth engagement on the Internet.

Abstract: This study examines the JUNIOR SUMMIT online community, which consisted of 3,062 adolescents representing 139 countries, varying SES, and a range of experience with computers. The online forum culminated in the election of 100 delegates. By analyzing the messages posted before results of the election were announced, we explore whether language use predicts who was elected as a leader, as well as gender differences in leadership style. Results indicate that the young online leaders do not adhere to adult leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 32 publications
(49 reference statements)
3
52
1
2
Order By: Relevance
“…Rainie, Horrigan and Cornfield (2005) found that the Internet has begun to serve as an information resource and as a tool for civic engagement and political participation among young Americans, being used in particular to gather political information. Cassell et al (2006) suggested that the online world may pull apart gender and traditional leadership, allowing more girls into leading positions and more similarities between boys and girls, reducing many gender stereotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Rainie, Horrigan and Cornfield (2005) found that the Internet has begun to serve as an information resource and as a tool for civic engagement and political participation among young Americans, being used in particular to gather political information. Cassell et al (2006) suggested that the online world may pull apart gender and traditional leadership, allowing more girls into leading positions and more similarities between boys and girls, reducing many gender stereotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The different studies do seem to agree that it is not only the quantity of communication that predicts the appearance of leader but rather the content and quality of the communication (Balthazard et al, 2009;Cassell, Huffaker, Tversky, & Ferriman, 2006;Sarker, Grewal, & Sarker, 2002), such that: work today in the world is dominated by computer-mediated communication, and this communication is common in virtual teams. However, the mere transmission of information from point A to point B is not sufficient.…”
mentioning
confidence: 99%
“…Finally, Cassell, Huffaker, Tversky, and Ferriman (2006) analyze leadership from a perspective of age and confirm through the analysis of messages sent and their use of language that they can predict the choice of the leader. Gender differences also predict leadership style.…”
mentioning
confidence: 99%
“…Tal comportamento faz com impulsione o desenvolvimento da juventude no que se refere a comunicação, liderança, socialização, informação e aprender em escala internacional. Os adolescentes usam a Internet como fonte de informações de saúde com o intuito de obter as informações necessárias no âmbito sexual e problemas de saúde, que eles provavelmente não têm acesso no local onde vivem (CASSELL et al, 2006). Nos últimos anos, em uma pesquisa recente mostraram que os estudos das ramificações da internet aumentaram muito.…”
Section: Vantagens E Desvantagens Constatadas Na Utilização Da Tecnolunclassified